ANALYSIS OF THE SUITABILITY AND CARRYING CAPACITY OF MANGROVE ECOTOURISM DUALAUS VILLAGE BELU REGENCY EAST NUSA TENGGARA PROVINCE - Ledheng, Ludgardis; Dewi, Ni Putu Yuni A; Hale, Maria (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Ecotourism is a form of tourism that contains conservation principles. The establishment of mangrove areas in Dualaus Village for ecotourism activities is the right strategy for ecosystem sustainability because it is ecologically and economically beneficial for the local community. However, efforts as an ecotourism area require an assessment of the suitability of ecotourism and the carrying capacity of the area. The purpose of this study is to assess the suitability of ecotourism and physical carrying capacity, so it can be used as a guideline for mangrove ecotourism management policies. Data collection is done through surveys and observations. Data are analyzed spatially with a Geographic Information System (GIS) approach that refers to the mangrove ecotourism suitability matrix. Furthermore, it proceeds with an assessment of the carrying capacity of the area to determine the number of visitors that can be accommodated. The results show that the ecotourism suitability index at the research site is a suitable category of 23.5 hectares, consisting of ESI 82.33% covering 15.5 ha and ESI 69.67% covering 8 ha. While an area of 5 ha is categorized as conditionally suitable with an ESI of 44.67%. Based on physical conditions, the carrying capacity for tracking activities is of 45 people/day, fishing of 199 people/day, picnicking of 158 people/day, and bird watching of 9 people/day. The total calculation of the carrying capacity of the ecotourism area is 459 people/day. Meanwhile, the real conditions in the field show 260 people/day. This informs that the number of tourists in the Dualaus Village ecotourism area does not exceed the maximum threshold. With this concept, it will be able to reduce the occurrence of damage to natural resources and the environment.